Inflammatory response and biomechanical properties of coaxial scaffolds for engineered skin in vitro and post-grafting. (15th October 2018) - Blackstone, Britani N.; Hahn, Jennifer M.; McFarland, Kevin L.; DeBruler, Danielle M.; Supp, Dorothy M.; Powell, Heather M.
Graphical abstract: Abstract: Engineered skin (ES) offers many advantages over split-thickness skin autografts for the treatment of burn wounds. However, ES, both in vitro and after grafting, is often significantly weaker, less elastic and more compliant than normal human skin. Biomechanical properties of ES can be tuned in vitro using electrospun co-axial (CoA) scaffolds. To explore the potential for coaxial scaffold-based ES use in vivo, two CoA scaffolds were fabricated with bioactive gelatin shells and biodegradable synthetic cores of polylactic acid (PLA) and polycaprolactone (PCL), and compared with gelatin monofilament scaffolds. Fibroblast and macrophage production of inflammatory cytokines interleukin 6 (IL-6) and transforming growth factor β-1 was significantly higher when cultured on PLA and PCL monofilament scaffolds compared to gelatin monofilament scaffolds. The core-shell fiber configuration significantly reduced production of pro-inflammatory cytokines to levels similar to those of gelatin monofilament scaffolds. In vitro, ES mechanical properties were significantly enhanced using CoA scaffolds; however, after grafting CoA- and gelatin-based ES to full-thickness excisional wounds on athymic mice, the in vitro mechanical advantage of CoA grafts was lost. A substantially increased inflammatory response to CoA-based ES was observed, with upregulation of IL-6 expression and a significant M2 macrophage presence. Additionally, expression of matrix metalloproteinase I was upregulated and collagen type I alpha 1 was downregulated in CoA ES two weeks after grafting. These results suggest that while coaxial scaffolds provide the ability to regulate biomechanics in vitro, further investigation of the inflammatory response to core materials is required to optimize this strategy for clinical use. Statement of Significance: Engineered skin has been used to treat very large burn injuries. Despite its ability to heal these wounds, engineered skin exhibits reduced biomechanical properties making it challenging to manufacture and surgically apply. Coaxial fiber scaffolds have been utilized to tune the mechanical properties of engineered skin while maintaining optimal biological properties but it is not known how these perform on a patient especially with regards to their inflammatory response. The current study examines the biomechanical and inflammatory properties of coaxial scaffolds and uniaxial scaffolds in vitro and in vivo . The results show that the biological response to the scaffold materials is a critical determinant of tissue properties after grafting with reduced inflammation and rapid scaffold remodeling leading to stronger skin.